Association of the complement factor H gene variants and ischemic stroke in Armenian population - A. S. Stepanyan (ՀՀ ԳԱԱ հրատ.)
Complement factor H (CFH) is a serum glycoprotein that regulates the function of the alternative complement pathway, sequence variations in the CFH gene are linked to many inflammatory and neovascular diseases. In the present study, we evaluated the potential association of the CFH rs800292, rs1061170, rs434535 single nucleotide polymorphisms (SNPs) with ischemic stroke (IS) in an Armenian population. In total, 136 patients with IS and 225 healthy subjects (controls) were involved in this study. Genomic DNA samples of ischemic stroke patients and controls were genotyped for CFH gene rs800292, rs1061170, rs434535 SNPs using polymerase chain reaction with sequence specific primers (PCR-SSP). Data were analyzed by Pearson’s χ 2 test. There was a significant decrease in the frequencies of rs800292*A minor allele (p=0.01, pcorr=0.03) and carriage of this allele (p=0.006, pcorr=0.018) in IS patients compared with healthy controls. According to the results rs1061170*C and rs424535*A minor alleles frequencies were higher in patients than in controls (p=3.0E-6, pcorr=9.0E-6 and p=2.1E-5, pcorr=6.3E-5 respectively). Moreover, the carriers of these alleles were overrepresented in patients compared to controls (p=0.0002, pcorr=0.0006 and p=8.0E-6, pcorr=2.4E-5 respectively). The results obtained implicated CFH gene rs800292, rs1061170, rs434535 SNPs in pathogenesis of ischemic stroke. In particular, it was shown that the CFH rs1061170*C and rs424535*A minor alleles are positively associated with IS, rs800292*A minor allele is a protective factor for IS at least in Armenian population.
Keywords: Biology; Molecular Biology